Investigations on the field bio-efficacy of some newer insecticides against insect pests of brinjal (Solanum melongena L.) - Sunda, N. R.; Kumar, Ashok; Bajpai, N.K.; Mandarwal, Neelam (Annals of Agricultural Research, 2016)
A field trial was conducted to investigate the field bio efficacy of some newer insecticides againstinsect pests of brinjal at horticultural farm Rajasthan College of Agriculture, Udaipur duringAugust-December 2008. Spirotetramat + imidacloprid @ 75 + 75 g a.i./ha was found most effectivefor the control of jassids and white flies as it accounted more than 76.11 per cent control, evenafter fourteen days of spraying. Imidacloprid 200 SL @ 75 g a.i./ha was found better than othertreatments in reducing jassids and white flies population which was statistically at par withspirotetramat + imidacloprid @ 60 + 60 g a.i./ha. Spirotetramat 150 SC @ 75 g a.i./ha wasadjudged most superior for the control of brinjal shoot and fruit borer. Dicofol and imidaclopridproved to be the least effective and flubendiamide gave moderate control of shoot and fruitborer which was at par with beta-cyfluthrin. Ready mixture of spirotetramat + imidaclopridand all the other insecticides did not show any photo toxic effect on brinjal plants.